THE INFLUENCE OF TOPOGRAPHY, NUMBER OF DEPENDENTS AND AGE OF HARVESTERS ON INCOME SATISFACTION OF PALM PALM HARVESTERS AT PRAPAT RANTAU GARDEN PTPN III - Mangaraja SP Lumban Gaol; Zulkarnain Lubis; Erwin Nyak Akoeb (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
PTPN III Rantauprapat Estate in Labuhan Batu Regency is engaged in plantations that manage the cultivation of oil palm and rubber plants and the Rubber Processing Plant (PPK) industry. Harvesting is one of the most important activities in the cultivation of oil palm plants, therefore the income satisfaction of harvesting employees needs attention from the company. The purpose of this study was to analyze the effect of Topography, Number of dependents and Age of harvesters on Income Satisfaction of Oil Palm Harvesters in the Rantau Prapat PTPN III Plantation. This study uses multiple linear analysis and cross tabulation test analysis between topographic factors, age and number of dependents of harvesters with income satisfaction. The results showed R Square of 0.595 or 59.50% topography variables, age and number of dependents affect income satisfaction. From the results of the analysis it is concluded that the type of topography, age and number of dependents of employees affect the income satisfaction of oil palm harvesters in the Rantauprapat Plantation of PTPN III. The positive work environment of the company as well as the level of experience and the level of expectations have a positive effect on employee income satisfaction.